Sosialisasi Kepercayaan Diri Pada Penyandang Disabilitas Fisik di Sentra Budi Perkasa Palembang - Anugerah, Kemala; Mawardah, Mutia (Jurnal Pengabdian Inovasi Masyarakat Indonesia, 2025)
People with physical disabilities are a group of people who often face multidimensional challenges, both physically, socially, and psychologically. The method used in this community service project was interviews and observation to obtain information related to the self-confidence of adolescents with physical disabilities. The results of this community service indicate that self-confidence is influenced by internal factors (such as self-concept, self-esteem, appearance, and life experiences) and external factors (such as education, social support, and family conditions). Subject AJ experienced low self-confidence and feelings of despair due to a combination of physical limitations, social pressure, and family economic conditions. This sense of despair reflects a deep psychological condition, characterized by the loss of hope and the inability to view the future positively.